Parents' Positive Behavior in Children in Online Learning at Sds Rancakasumba - Wangi, Risfa Mustifa; Saputra, Renda Sandi (International Journal of Ethno-Sciences and Education Research, 2022)
The existence of COVID-19 pandemic struck across the country in the world, including Indonesia has disrupted human activities in various sectors of life. Online learning can not be separated from internet networks. The internet network connection is one of the obstacles that the students live in the suburbs. The problem with online learning during the COVID-19 pandemic is environmental incompatibility by changing old habits so that parents do various ways so that parents can provide positive behavior toward children. This paper focuses on a positive behavior model in parents as an essential part of online learning by children amid the uncertainty of the end of the COVID-19 pandemic. The method in this paper is a literature study or literature review on positive behavior with logical model analysis. The results show that the factors that influence parents' positive behavior towards children in online learning amid the COVID-19 pandemic must fulfill the elements of confidence, hope, optimism, resilience, and intelligence of parents in responding to online learning carried out by their parent’s children. In addition, social capital as an alternative strengthens parents' positive behavior towards children so that they feel comfortable with the presence of parents to accompany online learning.